2005
DOI: 10.1210/jc.2005-0939
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity in Body Fat Distribution in Patients with Atypical Werner’s Syndrome Due to Heterozygous Arg133Leu Lamin A/C Mutation

Abstract: Atypical Werner's syndrome associated with Arg133Leu mutation in the LMNA gene presents with a phenotypically heterogeneous disorder. Furthermore, the severity of metabolic complications seems to correlate with the extent of lipodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 27 publications
0
36
1
4
Order By: Relevance
“…They are often correlated with the severity of the complications within patients carrying the same LMNA mutations [53,54]. For instance, we reported two female patients, one AfricanAmerican and one Caucasian, who shared the same R133L mutation but had vastly different body fat distribution.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…They are often correlated with the severity of the complications within patients carrying the same LMNA mutations [53,54]. For instance, we reported two female patients, one AfricanAmerican and one Caucasian, who shared the same R133L mutation but had vastly different body fat distribution.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, we reported two female patients, one AfricanAmerican and one Caucasian, who shared the same R133L mutation but had vastly different body fat distribution. The extent of the lipodystrophy appeared to be correlated with the severity of the metabolic complications and also the degree of abnormal nuclear morphology [53]. A study examining three homozygotes for the R527H mutation and the same clinical phenotype demonstrated that the extent of nuclear and heterochromatin irregularities were correlated with pre-lamin A accumulation and, interestingly, patient age [54].…”
Section: Discussionmentioning
confidence: 94%
“…Some patients with MAD do not have mutations in either of these two loci suggesting the presence of additional loci. Both partial and generalized lipodystrophy has also been reported in patients with Hutchinson-Gilford progeria [30], and atypical progeroid syndrome due to heterozygous LMNA mutations [31]. In patients with neonatal progeroid syndrome, generalized diminution of subcutaneous fat has been reported, but it is often accompanied by concomitant reduction in skeletal muscle and lean body mass unlike other lipodystrophy syndromes [32].…”
Section: Lipodystrophy In Association With Other Syndromesmentioning
confidence: 99%
“…6D). The lamin A-R133L mutation is a dominant mutation found in patients with Werner's syndrome, which affects the structure of the lamina (Jacob et al, 2005). The lamin A-R220Q dominant mutation is localized at the variable linker L12, which connects the 1B and 2A α-helical segments found in various laminopathies (Dhe-Paganon et al, 2002;Broers et al, 2006).…”
Section: Telomeres Form Aggregates In Senescent Hmscsmentioning
confidence: 99%